Design, analysis and fabrication of mini belt sander / Azad Hazim Bahrulashikin - Bahrulashikin, Azad Hazim (2022)
Mini belt sander is a tool that is expected to change the way people make finishing for their handcrafts or some daily tasks. There are some problems that lead to this project research. Firstly, most of sanding machines are relatively big especially when handling smaller projects. Secondly, plenty of sanding machines are quite expensive and not everyone could easily afford one. This project research is intended to make a more convenient and practical sanding machine because its compact form factor. Other than that, it is to make a sanding machine more affordable for users that are making a project for hobby or education purposes a better quality finishing. The methodologies used for this project includes problem understanding, reviewing literature, data collecting, data analyzing and solution drawing. This project is expected to be successful and convenience for most users.